2015
DOI: 10.1016/j.eats.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Superior Capsular Reconstruction for Treatment of Massive Irreparable Rotator Cuff Tears

Abstract: Massive irreparable rotator cuff tears have been troublesome entities to treat, especially in younger patients. Few good options exist, leaving most patients in recent years receiving a reverse total shoulder arthroplasty. Reverse shoulder arthroplasty carries serious risks, a limited lifespan, and no other viable options should it fail. Recent biomechanical studies have shown that the superior capsule is critical to containing the glenohumeral joint reduced, allowing the larger muscles like the deltoid and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
169
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(173 citation statements)
references
References 17 publications
0
169
0
4
Order By: Relevance
“…After a minimum follow-up period of 2 years, all clinical outcomes scores significantly improved: the American Shoulder and Elbow Surgeons score improved from 23.5 preoperatively to 92.9 postoperatively, and muscle strength significantly improved as well. Subsequently, Hirahara et al reported technical feasibility of acellular dermal allograft usage [10]. Burkhart et al identified advantages of SCR over reverse shoulder arthroplasty: (very) low infection rate, lower cost, and low morbidity [12].…”
Section: Highlight By Kotaro Yamakadomentioning
confidence: 99%
See 1 more Smart Citation
“…After a minimum follow-up period of 2 years, all clinical outcomes scores significantly improved: the American Shoulder and Elbow Surgeons score improved from 23.5 preoperatively to 92.9 postoperatively, and muscle strength significantly improved as well. Subsequently, Hirahara et al reported technical feasibility of acellular dermal allograft usage [10]. Burkhart et al identified advantages of SCR over reverse shoulder arthroplasty: (very) low infection rate, lower cost, and low morbidity [12].…”
Section: Highlight By Kotaro Yamakadomentioning
confidence: 99%
“…In the original description of SCR, autograft fascia lata was harvested from the patient's thigh. As an alternative idea, acellular dermal allograft has been used [10][11][12]. The graft is attached medially to the superior glenoid and laterally to the greater tuberosity, arthroscopically.…”
Section: Highlight By Kotaro Yamakadomentioning
confidence: 99%
“…Nearly all grafts have 5 mm added to the anterior, posterior, and medial dimensions to prevent suture pullout. A caveat to these measurements is that while some authors measure the corners of the prepared glenoid and greater tuberosity footprints [62], others place anchors first, then measure the distances between them [3,11,60,64,67]. Hirahara argues that use of the latter method creates a more accurate graft size that better matches the defect [60].…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…A caveat to these measurements is that while some authors measure the corners of the prepared glenoid and greater tuberosity footprints [62], others place anchors first, then measure the distances between them [3,11,60,64,67]. Hirahara argues that use of the latter method creates a more accurate graft size that better matches the defect [60]. On the lateral edge of the graft, a range of 5-15 mm is described [3,60,62,64,67], with greater sizes being used to more adequately cover and interface with the prepared greater tuberosity footprint.…”
Section: Surgical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation